Integration of automated information systems and architectural solutions in industrial enterprises - Vasileva, Viktoria; Kukartsev, Vladislav; Suprun, Elena; Shalaeva, Daria; Ageev, Daniel (E3S web of conferences, 2023)
The global aluminum industry faces challenges like price fluctuations and environmental regulations. To overcome these, it must adopt Automated Information Systems (AIS) to streamline data handling and improve decision-making. However, AIS implementation requires system integration, workforce training, and robust security measures. In summary, AIS adoption is crucial for the aluminum industry's efficiency and sustainability in a changing global landscape